Manajemen pengetahuan dalam melestarikan tradisi Seren Taun di Cigugur Kuningan - Apriyana, Fina; Khadijah, Ute Lies Siti; Rodiah, Saleha; Berliana, Naresh Aurelia (Faculty of Communication, Padjadjaran University, 2025)
Seren Taun is an important traditional ceremony in Cigugur, Kuningan Regency, rich in cultural values and local wisdom. However, the continuity of this tradition faces challenges in the modern era. This study aims to examine knowledge management in preserving Seren Taun in Cigugur, Kuningan. Using a qualitative approach with a case study design, data were collected through observations, interviews with indigenous people, the Seren Taun committee, and community leaders, as well as document studies. The results showed that human aspects (knowledge and expertise of traditional elders, youth involvement), organizational aspects (the role of the Tri Mulya Tri Wikrama Foundation, the formation of committees), and technology (social media, digital platforms) play an important role in managing and passing on knowledge about Seren Taun. However, there are also challenges, such as the lack of systematic documentation and youth participation. This study recommends strategies to improve knowledge management in Seren Taun, such as developing a digital documentation system, cultural education programs for youth, and utilizing information technology for promotion and dissemination